Busy. Please wait.
or

Forgot Password?

Don't have an account?  Sign up
or

taken

why

Make sure to remember your password. If you forget it there is no way for StudyStack to send you a reset link. You would need to create a new account.

By signing up, I agree to StudyStack's Terms of Service and Privacy Policy.

Already a StudyStack user? Log In

Reset Password
Enter the email address associated with your account, and we'll email you a link to reset your password.

Remove ads
Don't know (0)
Know (0)
remaining cards (0)
Save
0:01

 Flashcards Matching Hangman Crossword Type In Quiz Test StudyStack Study Table Bug Match Hungry Bug Unscramble Chopped Targets

Embed Code - If you would like this activity on your web page, copy the script below and paste it into your web page.

Normal Size     Small Size show me how

# Hall's Review 3.2

### Final Review

QuestionAnswer
Define a tangent line The tangent line to the curve y = f(x) at the point P(c, f(c)) is that line through P with slope m= lim (as h approaches 0) (f(c+h)- f(c))/h proivided the limit exists and is not infiniety or negative infinity.
Define derivative The derivative of a function f is another function f’ whose value at any number x is f'(x) = lim(as h approaches 0) [f(x+h)- f(x)]/h
Thm. differenciability implies what? continuity; If f’(c) exist, the f is continuous at c
Thm: Constant Function Rule If f(x) = k, where k is a constant, then for any x, f’(x) = 0
Thm: Identity Function Rule If f(x) = x then f’(x) = 1
Thm: Power Rule If f(x) = x^n, where n is a positive integer, the f’(x) = nx^n-1; that is Dx(x^n) = nx^n-1
Thm: Constant Multiple Rule If k is a constant and f is a differentiable function, then (kf)’(x) = k * f’(x)
Thm: Sum Rule If f and g are differentiable functions, then (f+g)’(x) = f’(x) + g’(x)
Thm: Difference Rule If f and g are differentiable functions, then (f-g)’(x) = f’(x) - g’(x)
Thm: Product Rule If f and g are differentiable functions, then (f*g)’(x) = f(x)g’(x) + g(x)f’(x)
Thm: Quotient Rule Let f and g be differentiable functions with g(x) does not equal zero. Then (f/g)'(x) = [g(x)f'(x)-g'(x)f(x)]/(g(x))^2
Derivative of sin x cos x
Derivative of cos x -sin x
Derivative of tan x (sec x)^2
Derivative of cot x -(csc x)^2
Derivative of sec x sec x tan x
Derivative of csc x -csc x cot x
Thm. Chain Rule Let y = f(u) and u = g(x). If g is differentiable at x and f is differentiable at u = g(x), then the composite function f(g(x)) is differentiable at x and f(g(x))' = f'(g(x))g'(x)
Created by: agea